ANALSISIS GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Vahera, Delvi; Onsardi, Onsardi (Yayasan Insani Mandiri Santani, 2021)
This research was conducted at PT. Karya Sawitindo Mas Tanjung Alai Village, Lubuk Pinang District, Mukomuko Regency, Bengkulu Province. This research is a quantitative research. Where quantitative data is data in the form of numbers. This study discusses the influence of leadership style, motivation and work environment on job satisfaction of employees of PT. The work of Sawitindo Mas. The population in this study were 94 permanent employees of PT. The work of Sawitindo Mas. The sampling technique in this study is saturated sampling as many as 94 permanent employees. In this study the data collection method is by means of observation and questionnaires. The data analysis technique used instrument test analysis, classical assumption test, multiple linear analysis, coefficient of determination analysis and hypothesis testing. Based on the results of data analysis, the results showed that: 1) In partial the variables of Leadership Style, Motivation and Work Environment had an effect on job satisfaction of employees of PT. Karya Sawitindo Mas. As evidenced by tcount > ttable (3.463 > 1.661) and tsig < Î±= (0.001 < 0.050), tcount > ttable (2,290 > 1.661) and tsig < = (0.024 < 0.050), tcount > ttable ( 3.806 > 1.661) and tsig < = (0.000 < 0.050). 2) Simultaneously the variables of Leadership Style, Motivation and Work Environment affect the job satisfaction of PT. The work of Sawitindo Mas. As evidenced by Fcount of 36,514 with Ftable value of 2.71, namely (36,514 >2,71) and tsig <Î± =(0,000 <0,050) which means that the variables of Leadership Style (X1), Motivation (X2) and Work Environment (X3 ) together have a significant effect on Employee Job Satisfaction at PT. The work of Sawitindo Mas.Keywords: Leadership Style, Motivation, Work Environment, and Employee Job Satisfaction.